TAIL SPIN - Mercer, Sienna (London : Egmont, 2015)
The twins are in a spin. Justin's enjoying dance class with girlfriend, Riley. But if the football team find out, he's dead meat. He'll need some fancy footwork to get out of this one. Meanwhile, Daniel's really happy with Debi - but her dad is super suspicious of him, and completely convinced that werewolves exist! Can Daniel throw him off the scent.
Keywords: Children's stories, English